MOF (Metal Organic Framework) composite membrane for selectively adsorbing rhenium as well as preparation method and application of MOF composite membrane
By preparing a sulfonic acid-functionalized UiO-66 type metal-organic framework material and a MOF composite membrane crosslinked with polyvinylidene fluoride, the selectivity and acid resistance issues of rhenium resource recovery in copper smelting were solved, and the efficient recovery and separation of rhenium were achieved.
Patent Information
- Application Number
- CN202511492291.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-20
- Publication Date
- 2025-11-18
- Estimated Expiration
- 2045-10-20
AI Technical Summary
In existing copper smelting processes, rhenium resources are not effectively recycled and utilized, resulting in the loss of strategic resources. Furthermore, existing methods lack selective separation capabilities in highly acidic environments and have insufficient material tolerance.
A MOF composite membrane with selective rhenium adsorption was prepared by crosslinking sulfonic acid-functionalized UiO-66 metal-organic framework material with polyvinylidene fluoride, adding acid-resistant ionic liquid and aminosilane coupling agent, and then forming a membrane material with good acid resistance and high selectivity through electrospinning and curing.
Selective adsorption and separation of rhenium under highly acidic conditions were achieved, improving the acid resistance and mechanical strength of the material and enabling stable recovery of rhenium resources.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of copper smelting, in particular to a MOF composite membrane for selectively adsorbing rhenium and a preparation method and application thereof. BACKGROUND
[0002] Rhenium, a rare metal, mainly exists in copper-molybdenum ore and will enter copper smelting waste acid along with flue gas in the copper smelting process. At present, the treatment of copper smelting waste acid in the industry mainly focuses on the harmless disposal of arsenic, and the rhenium resource is not paid much attention to. Rhenium finally enters the hazardous waste landfill along with arsenic sulfide slag. This disposal mode not only causes the loss of strategic resources, but also increases the amount of hazardous waste.
[0003] In recent years, researchers have carried out a lot of research in the field of rhenium extraction from waste acid. For example, an amine-based membrane is used to filter rhenium-containing acidic waste liquid, and high-efficiency adsorption of rhenium is realized through affinity groups (CN105803208A). However, amine groups are prone to protonation to form ammonium salt under acidic conditions, and sulfate radicals will also attack amine group carbon bonds. Extraction process is a common rhenium extraction technology, which uses specific binding of organic extractant and rhenium acid radical, and then realizes the recovery of rhenium through backwashing (CN119956131A, CN102502855A). However, the extractant is prone to emulsification to produce a third phase under low concentration background, which destroys the stability of the phase interface. The resin adsorption method has good recovery effect on rhenium (CN119464782A), but the selectivity is insufficient in complex environmental background, and the ion competition is large. Under the background of high acidity and interference of impurities, the existing methods are difficult to balance the selective separation and material resistance. SUMMARY
[0004] The purpose of the present application is to provide a MOF composite membrane for selectively adsorbing rhenium and a preparation method and application thereof. The MOF composite membrane for selectively adsorbing rhenium provided by the present application can selectively adsorb rhenium in the treatment of waste acid, so as to realize the selective separation of rhenium, and the membrane has excellent acid resistance.
[0005] The present application provides a preparation method of a MOF composite membrane for selectively adsorbing rhenium, comprising the following steps: Disperse a sulfonic acid functionalized UiO-66 type metal organic framework material in a polyvinylidene fluoride solution to obtain a metal organic framework material dispersion liquid, Mix the metal organic framework material dispersion liquid with a crosslinking agent to perform crosslinking reaction, and then mix the obtained reaction liquid with an acid-resistant ionic liquid to obtain a spinning solution, Perform electrospinning on the spinning solution to obtain a silk membrane, After the silk membrane is immersed in an amino silane coupling agent solution and solidified, a MOF composite membrane for selectively adsorbing rhenium is obtained.
[0006] Optionally, the sulfonic acid-functionalized UiO-66 type metal-organic framework material is prepared by a method comprising the following steps: Zirconium source, sulfonic acid functional ligand, and terephthalic acid were added to a mixed solvent of N,N-dimethylformamide and acid, and the mixture was sonicated for 15-20 min, followed by a solvothermal reaction. The resulting reaction solution was then subjected to solid-liquid separation to obtain the sulfonic acid-functionalized UiO-66 precursor. The sulfonic acid-functionalized UiO-66 precursor was sequentially washed with N,N-dimethylformamide aqueous solution, replaced with ethanol solvent, and acidified, followed by drying and activation to obtain a sulfonic acid-functionalized UiO-66 type metal-organic framework material.
[0007] Optionally, the zirconium source is at least one selected from ZrCl4, ZrOCl4, and Zr(NO3)4; the sulfonic acid functional ligand is at least one selected from 2-sulfonic acid terephthalic acid and sodium 2-sulfonic acid terephthalate; and the acid is at least one selected from glacial acetic acid, formic acid, hydrochloric acid, and benzoic acid. The molar ratio of the zirconium source to the sulfonic acid functional ligand is 1:0.2-0.8, and the molar ratio of the zirconium source to terephthalic acid is 1:0.5-0.8. The volume ratio of N,N-dimethylformamide to acid is 9-11:1, and the ratio of zirconium source to mixed solvent is 1 mmol: 26-29 mL. The solvothermal reaction is carried out at 115-125℃ for 22-26 h.
[0008] Optionally, the volume ratio of N,N-dimethylformamide to water in the N,N-dimethylformamide aqueous solution is (3-4):1. The acidification involved washing the sulfonic acid-functionalized UiO-66 precursor, after ethanol solvent replacement, with a 0.1 M hydrochloric acid / ethanol solution. The drying process is vacuum drying, and the drying temperature is 140-160℃ for 4-8 hours. The activation is carried out in a protective atmosphere at a temperature of 180-220°C for 5-7 hours.
[0009] Optionally, the solvent of the polyvinylidene fluoride solution is N,N-dimethylformamide, and the concentration of the polyvinylidene fluoride solution is 12-15 wt%. The amount of the sulfonate-functionalized UiO-66 type metal-organic framework material used is 30-40 wt% of the amount of polyvinylidene fluoride in the polyvinylidene fluoride solution. The crosslinking agent is at least one of divinylbenzene and ethylene glycol dimethacrylate, and the amount of the crosslinking agent is 1.3-1.7 wt% of the amount of polyvinylidene fluoride in the polyvinylidene fluoride solution. The crosslinking reaction is carried out at room temperature for 25-40 minutes. The acid-resistant ionic liquid is [P] 66614 [OTf], wherein the amount of the acid-resistant ionic liquid used is 18-22 wt% of the sulfonic acid-functionalized UiO-66 type metal-organic framework material.
[0010] Optionally, the spinneret diameter of the electrospinning is 0.4-0.6 mm, the spinning voltage is 18-22 kV, the receiving distance is 15-18 cm, the spinning solution flow rate is 0.8-1.2 mL / h, and the thickness of the filament film is 140-160 μm. The aminosilane coupling agent in the aminosilane coupling agent solution includes at least one of 3-aminopropyltriethoxysilane and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, the concentration of the aminosilane coupling agent solution is 1.8-2.5 wt%, and the solvent of the 3-aminopropyltriethoxysilane solution is at least one of ethanol and isopropanol. The impregnation time is 25-40 min, the curing temperature is 60-80℃, and the curing time is 0.8-1.2 h.
[0011] The present invention also provides a MOF composite membrane for selectively adsorbing rhenium prepared by the preparation method described in any one of the above technical solutions.
[0012] The present invention also provides an application of the MOF composite membrane for selectively adsorbing rhenium described in the above technical solution in the recovery of rhenium from waste acid.
[0013] Optionally, the application includes the following steps: The waste acid after removing suspended solids is then subjected to arsenic removal to obtain solidified arsenic slag and arsenic-removed waste acid. After adjusting the pH of the arsenic-removed waste acid to 1.3-1.7, it is filtered through the MOF composite membrane that selectively adsorbs rhenium to obtain purified acid and the rhenium-adsorbing MOF composite membrane. The rhenium-adsorbed MOF composite membrane was backwashed sequentially with acidic washing solution, water, and alkaline washing solution to obtain a rhenium-rich solution.
[0014] Optionally, the arsenic removal includes the following steps: adjusting the pH of the waste acid to 3.5-4.5, then adding sodium phosphate to a concentration of 0.02-0.1 M, then adding ferric chloride solution dropwise until the arsenic concentration is below 80 mg / L, and then filtering; wherein the concentration of the ferric chloride solution is 0.5-1.0 M; The acidic washing solution is an acidic mixed aqueous solution of ethylenediaminetetraacetic acid (EDTA) and sodium chloride, wherein the concentration of EDTA is 0.09-0.11 M, the concentration of sodium chloride is 0.09-0.11 M, and the pH of the acidic mixed aqueous solution is 2-4. When backwashing with water, backwash until the washing solution is neutral. The alkaline washing solution is an alkaline mixed aqueous solution of ammonium chloride and ammonia, wherein the concentration of ammonium chloride is 0.09-0.11 M, the concentration of ammonia is 0.09-0.11 M, and the pH of the alkaline mixed aqueous solution is 8.8-9.2.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The MOF composite membrane for selective rhenium adsorption obtained by the preparation method of this invention introduces a sulfonic acid-functionalized UiO-66 type metal-organic framework material, making the MOF composite membrane negatively charged. Highly negatively charged arsenate and molybdate ions are prevented from entering the composite membrane pores due to electrostatic repulsion, while rhenium ions react with H+. + Rhenium acid is formed and enters the pores of the MOF composite membrane, forming strong hydrogen bonds with sulfonic acid groups, thus being adsorbed to achieve selective adsorption of rhenium. Furthermore, the introduction of sulfonic acid groups stabilizes Zr-O bonds, enhancing the stability of the MOF framework; crosslinking agents improve the acid resistance and mechanical strength of the polymer matrix itself; adding acid-resistant ionic liquids to the spinning solution improves the acid resistance of the MOF composite membrane; and the resulting filament membrane, after being impregnated in an aminosilane coupling agent solution and cured, introduces amine groups into the MOF composite membrane. The amine matrix is protonated, transforming into positively charged ammonium ions, which, together with the sulfonic acid groups, form a bipolar charge-assisted repulsion mechanism (i.e., the membrane simultaneously has positive and negative charged groups; the positive charge repels metal ions such as copper, lead, and zinc, while the negative charge repels anions). The aminosilane coupling agent, after curing, forms an organosilicon polymer network, in which the silicon-oxygen covalent bonds are relatively stable, making the MOF composite membrane more acid-resistant. Simultaneously, the surface organosilicon polymer network provides additional crosslinking and support, improving the mechanical strength of the MOF composite membrane. As described in the embodiments of the present invention, the MOF composite membrane for selectively adsorbing rhenium provided by the present invention can selectively adsorb rhenium in the treatment of waste acid, thereby achieving selective separation of rhenium. At the same time, the membrane has excellent acid resistance and can still stably remove rhenium during long-term operation. In addition, the filtered purified liquid can be used for sulfuric acid regeneration and copper and lead recovery. Detailed Implementation
[0016] The present invention will be described below through specific embodiments. Those skilled in the art will understand that the specific embodiments described below are for illustrative purposes only and do not limit the scope of the invention in any way. Furthermore, in the following embodiments, unless otherwise specified, the reagents and equipment used are commercially available. If specific processing conditions and methods are not explicitly described in the following embodiments, conditions and methods known in the art can be used for processing.
[0017] This invention provides a method for preparing a MOF (metal-organic framework) composite membrane that selectively adsorbs rhenium, comprising the following steps: A sulfonic acid-functionalized UiO-66 type metal-organic framework material was dispersed in a polyvinylidene fluoride solution to obtain a metal-organic framework material dispersion. The metal-organic framework material dispersion was mixed with a crosslinking agent to carry out a crosslinking reaction. The resulting reaction solution was then mixed with an acid-resistant ionic liquid to obtain a spinning solution. The spinning solution is subjected to electrospinning to obtain a silk film. After the silk membrane is impregnated in an aminosilane coupling agent solution and then cured, a MOF composite membrane that selectively adsorbs rhenium is obtained.
[0018] This invention introduces a sulfonic acid-functionalized UiO-66 type metal-organic framework material into a MOF composite membrane for selective adsorption of rhenium. This makes the MOF composite membrane negatively charged. Highly negatively charged arsenate and molybdate ions are prevented from entering the pores of the composite membrane due to electrostatic repulsion, while rhenium ions react with H+. + Rhenium acid is formed and enters the pores of the MOF composite membrane, forming strong hydrogen bonds with sulfonic acid groups, thereby being adsorbed to achieve selective adsorption of rhenium. In addition, the introduction of sulfonic acid groups can stabilize Zr-O bonds and enhance the stability of the MOF skeleton. Crosslinking agents can improve the acid swelling resistance and mechanical strength of the polymer matrix itself. Adding acid-resistant ionic liquids to the spinning solution can improve the acid resistance of the MOF composite membrane. After the resulting silk membrane is impregnated in an aminosilane coupling agent solution and cured, amino groups are introduced into the MOF composite membrane. The amino groups are protonated and transformed into positively charged ammonium ions, which can form bipolar charge synergistic repulsion with sulfonic acid groups. The aminosilane coupling agent cures to form an organosilicon polymer network, in which the silicon-oxygen covalent bonds are relatively stable, making the MOF composite membrane more acid-resistant. At the same time, the organosilicon polymer network on the surface can play an additional crosslinking and supporting role, improving the mechanical strength of the MOF composite membrane. When filtering acidic wastewater using the MOF composite membrane for selective rhenium adsorption provided by this invention, some hydrated metal cations have large ionic radii, making it difficult for them to enter the pores; simultaneously, under an acidic background, H... +It will preferentially occupy the negatively charged groups on the membrane surface to form a proton protective layer, reducing the binding of cations to the membrane surface; even if the metal cations and the negative charges of the MOF composite membrane attract each other, due to the large size of the metal cations, they will also adsorb on the surface of the MOF composite membrane, forming reversible surface adsorption, which is easy to wash off.
[0019] The present invention first disperses sulfonic acid-functionalized UiO-66 type metal-organic framework material in polyvinylidene fluoride solution to obtain metal-organic framework material dispersion.
[0020] The present invention does not have a specific limitation on the dispersion method, as long as a uniformly mixed dispersion can be obtained. In the embodiments of the present invention, ultrasonic dispersion is used, and the ultrasonic time is 20-30 min.
[0021] In some embodiments of the present invention, the sulfonic acid-functionalized UiO-66 type metal-organic framework material is prepared by a method comprising the following steps: Zirconium source, sulfonic acid functional ligand, and terephthalic acid were added to a mixed solvent of N,N-dimethylformamide and acid, and the mixture was sonicated for 15-20 min, followed by a solvothermal reaction. The resulting reaction solution was then subjected to solid-liquid separation to obtain the sulfonic acid-functionalized UiO-66 precursor. The sulfonic acid-functionalized UiO-66 precursor was sequentially washed with N,N-dimethylformamide aqueous solution, replaced with ethanol solvent, and acidified, followed by drying and activation to obtain a sulfonic acid-functionalized UiO-66 type metal-organic framework material.
[0022] In some embodiments of the present invention, the zirconium source is at least one selected from ZrCl4, ZrOCl4, and Zr(NO3)4; the sulfonic acid functional ligand is at least one selected from 2-sulfonic acid terephthalic acid and sodium 2-sulfonic acid terephthalate; and the acid is at least one selected from glacial acetic acid, formic acid, hydrochloric acid, and benzoic acid. When the acid is hydrochloric acid, the concentration of the hydrochloric acid is 1.0-1.5 M. In the present invention, the zirconium source provides a metal center for the metal-organic framework material, the sulfonic acid functional ligand provides sulfonic acid functional groups for the sulfonic acid metal-organic framework material, the terephthalic acid and zirconium ions can form a stable framework structure, and the acid provides protons to maintain the acidic environment in the initial stage of the reaction, which can inhibit excessive hydrolysis of the zirconium source and avoid the formation of disordered zirconium-oxygen clusters.
[0023] In some embodiments of the present invention, the molar ratio of the zirconium source to the sulfonic acid functional ligand is 1:0.2-0.8, preferably 1:0.2-0.4, and specifically can be 1:0.2, 1:0.3, 1:0.4, etc.; the molar ratio of the zirconium source to terephthalic acid is 1:0.5-0.8, preferably 1:0.6-0.8, and specifically can be 1:0.6, 1:0.7, 1:0.8, etc. In this invention, the above ratio further ensures that the obtained sulfonic acid-functionalized UiO-66 type metal-organic framework material has sufficient sulfonic acid functional groups, resulting in better adsorption performance of the obtained MOF composite membrane. In addition, when sulfonic acid groups are modified inside the MOF channels, they generate steric hindrance, preventing water molecules from approaching and attacking the active sites of Zr-O bonds, thus slowing down the hydrolysis reaction rate. The sulfonic acid groups themselves are hydrophilic, but the benzene rings they are connected to are hydrophobic, creating a local hydrophobic region that can repel water molecules from entering the channels, reducing the possibility of water molecules contacting Zr-O bonds, thereby stabilizing Zr-O bonds and enhancing the stability of the MOF framework.
[0024] In some embodiments of the present invention, the volume ratio of N,N-dimethylformamide to acid is 9-11:1, specifically 9:1, 10:1, 11:1, etc., and the ratio of zirconium source to mixed solvent is 1 mmol:26-29 mL, specifically 1 mmol:26 mL, 1 mmol:27 mL, 1 mmol:27.5 mL, 1 mmol:29 mL, etc. In this invention, maintaining the optimal ratio of N,N-dimethylformamide to acid ensures a high yield of large-sized UiO-66 precursors. Below this ratio, a high acid content results in a highly acidic system, potentially excessively inhibiting ligand deprotonation and coordination, leading to a lower product yield. Above this ratio, a low acid content results in insufficient concentration of the regulator (the acid anion competes with the ligand for zirconium sites, moderately slowing crystal nucleation and growth rates), causing excessively rapid crystal growth and the formation of small-sized crystals with numerous defects. A suitable ratio of zirconium source to mixed solvent maintains a high reaction rate while preventing agglomeration. Below this ratio, excessive solvent leads to low reaction concentration and a low reaction rate. Above this ratio, insufficient solvent may result in incomplete dissolution, poor product uniformity, and excessively rapid crystal nucleation and growth, easily leading to agglomeration.
[0025] In this invention, ultrasonication is performed before the solvothermal reaction, which makes the raw materials more uniformly mixed and dispersed, which is beneficial to the solvothermal reaction.
[0026] In some embodiments of the present invention, the solvothermal reaction is carried out at 115-125°C for 22-26 h, wherein the temperature of the solvothermal reaction can be 115°C, 120°C, 125°C, etc.; and the time of the solvothermal reaction can be 22 h, 24 h, 26 h, etc.
[0027] In some embodiments of the present invention, the volume ratio of N,N-dimethylformamide to water in the N,N-dimethylformamide aqueous solution is (3-4):1. In this invention, washing with the N,N-dimethylformamide aqueous solution removes unreacted ligands and metal salts, while ethanol solvent displacement displaces the N,N-dimethylformamide from the pores of the precursor, facilitating the subsequent drying process. The present invention does not specifically limit the number of washes with the N,N-dimethylformamide aqueous solution; those skilled in the art can determine this based on the washing process. In this embodiment, the washing is performed three times. The present invention does not specifically limit the method of ethanol solvent displacement, as long as the purpose of solvent displacement is achieved. In this embodiment, the ethanol solvent displacement is performed by ethanol washing, and the washing is performed three times.
[0028] In some embodiments of the present invention, the acidification involves washing the sulfonic acid-functionalized UiO-66 precursor after ethanol solvent replacement with a 0.1 M hydrochloric acid / ethanol solution; the 0.1 M hydrochloric acid / ethanol solution is obtained by diluting 0.83 mL of concentrated hydrochloric acid (12 M) with ethanol to 100 mL. In the present invention, the acidification converts the sulfonic acid groups in the precursor from salt form to acid, ensuring that the sulfonic acid groups on the final UiO-66 type metal-organic framework material are in acid form, thereby selectively adsorbing rhenium ions.
[0029] In some embodiments of the present invention, the drying is vacuum drying, the drying temperature is 140-160°C, specifically 140°C, 150°C, 160°C, etc., and the drying time is 4-8 hours, specifically 4 hours, 6 hours, 8 hours, etc. In the present invention, vacuum drying can remove most of the free solvent in the surface and pores.
[0030] In some embodiments of the present invention, the activation is carried out in a protective atmosphere, and the activation temperature is 180-220°C, specifically 180°C, 200°C, 220°C, etc.; the activation time is 5-7 hours, specifically 5 hours, 6 hours, 7 hours, etc. In the present invention, unless otherwise specified, the protective atmosphere refers to a chemically inert gas, such as nitrogen, argon, etc. In the embodiments of the present invention, the protective atmosphere is a nitrogen atmosphere. In the present invention, the activation under a protective atmosphere can overcome the interaction force between solvent molecules and pore walls, achieve complete opening of the pores, and thoroughly remove residual solvent.
[0031] In some embodiments of the present invention, the solvent of the polyvinylidene fluoride (PVDF) solution is N,N-dimethylformamide (DMF), and the concentration of the PVDF solution is 12-15 wt%. In the present invention, PVDF is the matrix of the composite membrane, and MOF particles and ionic liquid are dispersed and embedded in the matrix. During the subsequent crosslinking process, the alkenyl functional groups in the crosslinking agent abstract hydrogen atoms from PVDF, forming covalent bridges between PVDF molecular chains to achieve chemical crosslinking. At the above concentration, the PVDF / DMF solution has suitable viscosity and surface tension. Below this range, the viscosity is low, the jet is easily broken, continuous fiber formation is impossible, and mechanical properties are poor. Above this range, the viscosity is high, the flowability is poor, and spinning is difficult. The present invention does not have a special limitation on the method of obtaining the PVDF solution; any solution in which the PVDF is completely dissolved is acceptable. In the embodiments of the present invention, PVDF is obtained by dispersing it in N,N-dimethylformamide and stirring at 60°C for 6 h.
[0032] In some embodiments of the present invention, the amount of the sulfonic acid-functionalized UiO-66 type metal-organic framework material is 30-40 wt% of the amount of polyvinylidene fluoride (PVDF) in the PVDF solution, specifically 30 wt%, 35 wt%, 40 wt%, etc. In this invention, this dosage range ensures that the composite membrane possesses both good adsorption capacity and mechanical properties. Below this range, there are insufficient adsorption sites within the membrane, resulting in low adsorption capacity; above this range, the MOF is unevenly dispersed, the fibers are easily broken, and the mechanical strength is low.
[0033] After obtaining the metal-organic framework material dispersion, this invention mixes the metal-organic framework material dispersion with a crosslinking agent to carry out a crosslinking reaction. Then, the resulting reaction solution is mixed with an acid-resistant ionic liquid to obtain a spinning solution. In this invention, through crosslinking, the crosslinking agent polymerizes to form a three-dimensional network structure and grafts onto PVDF molecular chains, further enhancing the acid swelling resistance and mechanical strength of the polymer matrix itself.
[0034] In some embodiments of the present invention, the crosslinking agent is at least one of divinylbenzene and ethylene glycol dimethacrylate, and the amount of the crosslinking agent is 1.3-1.7 wt% of the amount of polyvinylidene fluoride in the polyvinylidene fluoride solution, specifically 1.3 wt%, 1.5 wt%, 1.7 wt%, etc. In the present invention, the above-mentioned amount of crosslinking agent can achieve effective crosslinking while avoiding embrittlement caused by excessive crosslinking. If the amount is too low, the degree of crosslinking is insufficient, and the effect of improving acid resistance is not obvious; if the amount is too high, the film lacks flexibility.
[0035] In some embodiments of the present invention, the crosslinking reaction is carried out at room temperature, and the crosslinking reaction time is 25-40 min, specifically 25 min, 30 min, 35 min, 40 min, etc.
[0036] In some embodiments of the present invention, the acid-resistant ionic liquid is [P 66614 [OTf] (i.e., cationic trihexyltetradecylphosphonium (P66614)) + ) and anionic trifluoromethanesulfonate (OTf) - The acid-resistant ionic liquid is composed of 18-22 wt% of the sulfonic acid-functionalized UiO-66 type metal-organic framework material, specifically 18 wt%, 20 wt%, 22 wt%, etc. In this invention, the acid-resistant ionic liquid can improve the corrosion resistance of the MOF composite film.
[0037] After obtaining the spinning solution, the present invention performs electrospinning on the spinning solution to obtain a silk film.
[0038] In some embodiments of the present invention, the diameter of the spinneret in the electrospinning is 0.4-0.6 mm, specifically 0.4 mm, 0.5 mm, 0.6 mm, etc.; the spinning voltage is 18-22 kV, specifically 18 kV, 20 kV, 22 kV, etc.; the receiving distance is 15-18 cm, specifically 15 cm, 16 cm, 17 cm, 18 cm, etc.; the spinning solution flow rate is 0.8-1.2 mL / h, specifically 0.8 mL / h, 1.0 mL / h, 1.2 mL / h; the thickness of the filament film is 140-160 μm, specifically 140 μm, 150 μm, 160 μm, etc. In embodiments of the present invention, the number of filaments in the filament film is 140-160, specifically 140, 150, 160, etc.
[0039] After obtaining the silk membrane, the present invention impregnates the silk membrane in an aminosilane coupling agent solution and then cures it to obtain a MOF composite membrane that selectively adsorbs rhenium.
[0040] In some embodiments of the present invention, the aminosilane coupling agent (i.e., an amino-containing silane coupling agent) in the aminosilane coupling agent solution includes at least one of 3-aminopropyltriethoxysilane and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, and the concentration of the aminosilane coupling agent solution is 1.8-2.5%, specifically 1.8%, 2.0%, 2.5%, etc.; the solvent of the aminosilane coupling agent solution is at least one of ethanol and isopropanol. In the present invention, the above-mentioned concentration of aminosilane coupling agent solution ensures that the aminosilane coupling agent is uniformly distributed on the silk film, forming sufficient amino functional groups while avoiding excessive intermolecular condensation due to excessive concentration.
[0041] In some embodiments of the present invention, the impregnation time is 25-40 min; after the impregnation is completed, the impregnated film is removed and cured; the curing temperature is 60-80℃, specifically 60℃, 75℃, 80℃, etc.; the curing time is 0.8-1.2 h, specifically 0.8 h, 1.0 h, 1.2 h, etc. In this invention, 3-aminopropyltriethoxysilane can be uniformly loaded onto a silk membrane through impregnation. During the curing process, 3-aminopropyltriethoxysilane undergoes a hydrolysis-condensation reaction, and its ethoxy groups react with water to generate active silanol groups. The active silanol groups condense with the hydroxyl groups (on the MOF metal clusters) on the membrane surface to form covalent bonds on the silicon-oxygen surface. The silanol groups also condense with each other to form a silicon-oxygen-silicon structure. Finally, amine groups are firmly grafted onto the membrane surface through covalent bonds to form an organosilicon polymer network with terminal amine groups. At the same time, the silicon-oxygen covalent bonds are relatively stable, making the membrane more acid-resistant. The silane network on the membrane surface can play an additional cross-linking and supporting role, improving the mechanical strength of the membrane.
[0042] After curing, the present invention preferably washes the cured MOF film with water to remove impurities.
[0043] In another aspect, the present invention provides a MOF composite membrane for selectively adsorbing rhenium prepared by any of the preparation methods described in the above-mentioned technical solutions.
[0044] The present invention also provides the application of the MOF composite membrane for selectively adsorbing rhenium described in the above technical solution in the recovery of rhenium from waste acid.
[0045] In some embodiments of the present invention, the application includes the following steps: The waste acid after removing suspended solids is then subjected to arsenic removal to obtain solidified arsenic slag and arsenic-removed waste acid. After adjusting the pH of the arsenic-removed waste acid to 1.3-1.7, it is filtered through the MOF composite membrane that selectively adsorbs rhenium to obtain purified acid and the rhenium-adsorbing MOF composite membrane. The rhenium-adsorbed MOF composite membrane was backwashed sequentially with acidic washing solution, water, and alkaline washing solution to obtain a rhenium-rich solution.
[0046] In this invention, arsenic is first removed from the waste acid. The waste acid after arsenic removal contains a small amount of residual arsenate, while rhenium (in the form of rhenium ions) and most of the molybdate ions remain in the waste acid after arsenic removal. Then, the aforementioned MOF composite membrane that selectively adsorbs rhenium is used to filter the waste acid after arsenic removal. Rhenium can be selectively adsorbed on the MOF composite membrane. Although arsenate ions can also generate neutral arsenic acid, their molecules are too large to enter the pores due to spatial constraints. Molybdate ions generate molybdate, which easily polymerizes to form polymers. Due to their large size, they also cannot enter the pores. The hydrated ionic radii of some metal ions are also large, making it difficult for them to enter the pores. Therefore, residual arsenate ions, rhenium, and most of the molybdate ions are retained (arsenate ions and molybdate ions are in the concentrate that has not passed through the membrane (cross-flow filtration is used in the example)). Sulfate ions and metal cations pass through the MOF composite membrane with the fluid. The resulting purified acid solution can be used for sulfuric acid regeneration and copper and lead recovery.
[0047] The present invention does not have any special limitations on the source and water quality of the waste acid to be treated, and conventional waste acid can be treated; in the embodiments of the present invention, the water quality of the waste acid to be treated is as follows: rhenium 19.4 mg / L, arsenic 3.9 g / L, sulfate 150 g / L, molybdenum 13.2 mg / L, pH 2.1.
[0048] In some embodiments of the present invention, the arsenic removal includes the following steps: adjusting the pH of the waste acid to 3.5-4.5, then adding sodium phosphate to a concentration of 0.02-0.1 M, then adding ferric chloride solution dropwise until the arsenic concentration is below 80 mg / L, and then filtering. In conventional arsenic removal without adding sodium phosphate, Fe... 3+ Upon addition, ferric arsenate and ferric hydroxide are generated. Ferric hydroxide colloids adsorb rhenium ions, leading to rhenium loss. In this invention, the pH of the waste acid is first adjusted to 3.5-4.5 so that arsenic exists in the form of arsenic acid molecules. Then, sodium phosphate is added first, followed by ferric chloride, so that Fe... 3+ First with PO4 3- Ferric phosphate is generated, with ferric phosphate acting as a crystal nucleus, and then Fe is added. 3+ Fe will accumulate around ferric phosphate. 3+ It reacts with arsenate to form ferric arsenate, which is then coated on the outside of ferric phosphate, forming a ferric phosphate / ferric arsenate composite precipitate, thus avoiding the loss of rhenium.
[0049] The present invention does not have any particular limitation on the method of adjusting the pH of the waste acid, as long as the desired pH can be obtained. In the embodiments of the present invention, the pH of the waste acid is adjusted by adding calcium hydroxide.
[0050] In some embodiments of the present invention, the concentration of the ferric chloride solution is 0.5-1.0 M, specifically 0.5 M, 0.8 M, 1.0 M, etc. In an embodiment of the present invention, ferric chloride solution is first added according to a molar ratio of iron to arsenic of 1.1-1.5:1 (specifically 1.1:1, 1.2:1, 1.5:1, etc.), stirred at room temperature for 30-60 min, and then the arsenic content in the solution is detected. Based on the arsenic content, ferric chloride solution is added again and stirred for 30-60 min. This operation (i.e., adding ferric chloride solution - stirring for 30-60 min) is repeated until the arsenic concentration is below 80 mg / L.
[0051] In some embodiments of the present invention, the acidic washing solution is an acidic mixed aqueous solution of ethylenediaminetetraacetic acid (EDTA) and sodium chloride. The concentration of EDTA is 0.09-0.11 M, specifically 0.09 M, 0.1 M, 0.11 M, etc.; the concentration of sodium chloride is 0.09-0.11 M, specifically 0.09 M, 0.1 M, 0.11 M, etc.; and the pH of the acidic mixed aqueous solution is 2-4. The present invention does not specifically limit the method of adjusting the pH of the acidic washing solution; conventional adjustment methods are sufficient, such as adding sodium hydroxide or sulfuric acid. In the present invention, during the backwashing process of the acidic washing solution, EDTA can form complexes with various metal cations, stripping them from the membrane; sodium chloride can provide ionic strength, weakening the electrostatic interaction between the membrane and contaminants. In some embodiments of the present invention, when backwashing with water, the backwash is performed until the washing solution is neutral, thereby reducing damage to the membrane.
[0052] In some embodiments of the present invention, the alkaline washing solution is an alkaline mixed aqueous solution of ammonium chloride and ammonia, wherein the concentration of ammonium chloride is 0.09-0.11 M, specifically 0.09 M, 0.1 M, 0.11 M, etc.; the concentration of ammonia is 0.09-0.11 M, specifically 0.09 M, 0.1 M, 0.11 M, etc.; and the pH of the alkaline mixed aqueous solution is 8.8-9.2, specifically 8.8, 9.0, 9.2, etc. In the present invention, backwashing with the alkaline washing solution can remove rhenium ions from the composite membrane, thereby obtaining a rhenium-rich solution.
[0053] In this invention, it is preferable to backwash after the MOF composite membrane selectively adsorbs rhenium to saturation. Specifically, this can be determined by detecting the rhenium concentration and pH value in the purified acid solution. When the rhenium concentration in the purified acid solution is greater than 5% of the rhenium concentration in the waste acid to be filtered, the MOF composite membrane selectively adsorbs rhenium is considered to have reached saturation.
[0054] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments. The embodiments of this application are only examples, and all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0055] Example 1 (1) Preparation of MOF composite membranes that selectively adsorb rhenium: ZrCl4, 2-sulfonic terephthalic acid, and terephthalic acid were added to a DMF / glacial acetic acid (10:1 v / v) mixed solvent at a molar ratio of 1:0.2:0.8 (the ratio of ZrCl4 to the mixed solvent was 1 mmol:27.5 mL). The mixture was sonicated for 15 min until the solution was clear, then transferred to a reaction vessel and subjected to a solvothermal reaction at 120 °C for 24 h. After the reaction solution cooled to room temperature, it was centrifuged to obtain the precipitate, which was the sulfonic acid-functionalized UiO-66 precursor. The precursor was washed three times each with DMF aqueous solution (DMF to water volume ratio of 3:1) and ethanol, and then washed twice with 0.1 M hydrochloric acid / ethanol solution. It was then vacuum dried at 150 °C for 6 h and activated at 200 °C for 6 h under a nitrogen atmosphere to obtain the sulfonic acid-functionalized UiO-66 metal-organic framework material.
[0056] Polyvinylidene fluoride particles were added to N,N-dimethylformamide and stirred at 60°C for 6 h to dissolve the polyvinylidene fluoride, resulting in a polyvinylidene fluoride solution with a concentration of 12 wt%.
[0057] Sulfonic acid-functionalized UiO-66 type metal-organic framework material was added to a polyvinylidene fluoride solution and ultrasonically dispersed for 30 min. Then, divinylbenzene was added, and the mixture was stirred at room temperature for 30 min. Finally, [P] was added. 66614 [OTf], stirred at room temperature for 1 h to obtain a spinning solution, wherein the amount of sulfonic acid-functionalized UiO-66 type metal-organic framework material is 30 wt% of the amount of polyvinylidene fluoride in the polyvinylidene fluoride solution, and the amount of divinylbenzene is 1.5 wt% of the amount of polyvinylidene fluoride in the polyvinylidene fluoride solution, [P 66614 The amount of [OTf] used is 20 wt% of the sulfonic acid-functionalized UiO-66 type metal-organic framework material.
[0058] The spinning solution was injected into the feeding system of the electrospinning equipment (spinneret diameter of 0.5 mm), and spinning was carried out under the conditions of spinning voltage of 18 kV, receiving distance of 15 cm, and spinning solution flow rate of 1 mL / h to obtain a filament film with a thickness of 150 μm and a number of 150 filaments.
[0059] The silk membrane was immersed in a 2% APTES / ethanol solution for 30 min, then removed and cured at 60℃ for 1 h. It was then rinsed with pure water to obtain a MOF composite membrane that selectively adsorbs rhenium.
[0060] (2) Arsenic removal: In this embodiment, waste acid generated by a smelting enterprise was treated. The waste acid had the following water quality: rhenium 19.4 mg / L, arsenic 3.9 g / L, sulfate 150 g / L, molybdenum 13.2 mg / L, pH 2.1. The pH of the filtered waste acid was adjusted to 3.5 with calcium hydroxide, sodium phosphate was added to a concentration of 0.02 M, and then ferric chloride solution with a concentration of 0.5 M (where the molar ratio of iron to arsenic was 1.1:1) was added dropwise. The mixture was stirred at room temperature for 30 min. Depending on the arsenic concentration, ferric chloride solution was added and stirred for another 30 min. This operation was repeated until the arsenic concentration was below 80 mg / L. The mixture was then filtered to obtain solidified arsenic slag and arsenic-removed waste acid.
[0061] (3) Adjust the pH of the arsenic-removed waste acid to 1.5, and then filter it through the MOF composite membrane that selectively adsorbs rhenium (wherein, the membrane flux is 75 L / (m²)). 2 (·h), with a water flow rate of 318 mL / h, a MOF composite membrane for purifying acid and adsorbing rhenium was obtained.
[0062] (4) After adsorption saturation, the MOF composite membrane adsorbed with rhenium is backwashed with an acidic mixed aqueous solution of ethylenediaminetetraacetic acid and sodium chloride (concentration of ethylenediaminetetraacetic acid is 0.1 M, concentration of sodium chloride is 0.1 M, pH is 3), then backwashed with water until neutral, and finally backwashed with an alkaline mixed aqueous solution of ammonium chloride and ammonia (concentration of ammonium chloride is 0.1 M, concentration of ammonia is 0.1 M, pH is 9.0). The backwash liquid is collected to obtain rhenium-rich solution.
[0063] Example 2 (1) Preparation of MOF composite membranes that selectively adsorb rhenium: ZrCl4, 2-sulfonic terephthalic acid, and terephthalic acid were added to a DMF / glacial acetic acid (10:1 v / v) mixed solvent (ZrCl4 to mixed solvent ratio of 1 mmol:27.5 mL) at a molar ratio of 1:0.3:0.7. The mixture was sonicated for 15 min until the solution was clear, then transferred to a reaction vessel and subjected to a solvothermal reaction at 120 °C for 24 h. After the reaction solution cooled to room temperature, it was centrifuged to obtain the precipitate, which was the sulfonic acid-functionalized UiO-66 precursor. The precursor was washed three times each with DMF aqueous solution (DMF to water volume ratio of 4:1) and ethanol, and then washed twice with 0.1 M hydrochloric acid / ethanol solution. It was then vacuum dried at 150 °C for 6 h and activated at 200 °C for 6 h under a nitrogen atmosphere to obtain the sulfonic acid-functionalized UiO-66 metal-organic framework material.
[0064] Polyvinylidene fluoride particles were added to N,N-dimethylformamide and stirred at 60°C for 6 h to dissolve the polyvinylidene fluoride, resulting in a polyvinylidene fluoride solution with a concentration of 12 wt%.
[0065] Sulfonic acid-functionalized UiO-66 type metal-organic framework material was added to a polyvinylidene fluoride solution and ultrasonically dispersed for 30 min. Then, divinylbenzene was added, and the mixture was stirred at room temperature for 30 min. Finally, [P] was added. 66614 [OTf], stirred at room temperature for 1 h to obtain a spinning solution, wherein the amount of sulfonic acid-functionalized UiO-66 type metal-organic framework material is 30 wt% of the amount of polyvinylidene fluoride in the polyvinylidene fluoride solution, and the amount of divinylbenzene is 1.5 wt% of the amount of polyvinylidene fluoride in the polyvinylidene fluoride solution, [P 66614 The amount of [OTf] used is 20 wt% of the sulfonic acid-functionalized UiO-66 type metal-organic framework material.
[0066] The spinning solution was injected into the feeding system of the electrospinning equipment (spinneret diameter of 0.5 mm), and spinning was carried out under the conditions of spinning voltage of 18 kV, receiving distance of 15 cm, and spinning solution flow rate of 1 mL / h to obtain a filament film with a thickness of 150 μm and a number of 150 filaments.
[0067] The silk membrane was immersed in a 2% APTES / ethanol solution for 30 min, then removed and cured at 75℃ for 1 h. It was then rinsed with pure water to obtain a MOF composite membrane that selectively adsorbs rhenium.
[0068] (2) Arsenic removal: In this embodiment, waste acid generated by a smelting enterprise was treated. The waste acid had the following water quality: rhenium 19.4 mg / L, arsenic 3.9 g / L, sulfate 150 g / L, molybdenum 13.2 mg / L, pH 2.1. The pH of the filtered waste acid was adjusted to 4.0 with calcium hydroxide, sodium phosphate was added to a concentration of 0.05 M, and then ferric chloride solution with a concentration of 0.8 M (where the molar ratio of iron to arsenic was 1.2:1) was added dropwise. The mixture was stirred at room temperature for 40 min. Depending on the arsenic concentration, ferric chloride solution was added and stirred for another 40 min. This operation was repeated until the arsenic concentration was below 80 mg / L. The mixture was then filtered to obtain solidified arsenic slag and arsenic-removed waste acid.
[0069] (3) Adjust the pH of the arsenic-removed waste acid to 1.5, and then filter it through the MOF composite membrane that selectively adsorbs rhenium (wherein, the membrane flux is 75 L / (m²)). 2 (·h), with a water flow rate of 318 mL / h, a MOF composite membrane for purifying acid and adsorbing rhenium was obtained.
[0070] (4) After adsorption saturation, the MOF composite membrane adsorbed with rhenium is backwashed with an acidic mixed aqueous solution of ethylenediaminetetraacetic acid and sodium chloride (concentration of ethylenediaminetetraacetic acid is 0.1 M, concentration of sodium chloride is 0.1 M, pH is 3), then backwashed with water until neutral, and finally backwashed with an alkaline mixed aqueous solution of ammonium chloride and ammonia (concentration of ammonium chloride is 0.1 M, concentration of ammonia is 0.1 M, pH is 9.0). The backwash liquid is collected to obtain rhenium-rich solution.
[0071] Example 3 (1) Preparation of MOF composite membranes that selectively adsorb rhenium: ZrCl4, 2-sulfonic terephthalic acid, and terephthalic acid were added to a DMF / glacial acetic acid (10:1 v / v) mixed solvent at a molar ratio of 1:0.4:0.6 (ZrCl4 to mixed solvent ratio of 1 mmol:27.5 mL). The mixture was sonicated for 15 min until the solution was clear, then transferred to a reaction vessel and subjected to a solvothermal reaction at 120 °C for 24 h. After the reaction solution cooled to room temperature, it was centrifuged to obtain the precipitate, which was the sulfonic acid-functionalized UiO-66 precursor. The precursor was washed three times each with DMF aqueous solution (DMF to water volume ratio of 4:1) and ethanol, and then washed twice with 0.1 M hydrochloric acid / ethanol solution. It was then vacuum dried at 150 °C for 6 h and activated at 200 °C for 6 h under a nitrogen atmosphere to obtain the sulfonic acid-functionalized UiO-66 metal-organic framework material.
[0072] Polyvinylidene fluoride particles were added to N,N-dimethylformamide and stirred at 60°C for 6 h to dissolve the polyvinylidene fluoride, resulting in a polyvinylidene fluoride solution with a concentration of 15 wt%.
[0073] Sulfonic acid-functionalized UiO-66 type metal-organic framework material was added to a polyvinylidene fluoride solution and ultrasonically dispersed for 20 min. Then, divinylbenzene was added, and the mixture was stirred at room temperature for 30 min. Finally, [P] was added. 66614 [OTf], the spinning solution was obtained by slow stirring at room temperature for 1 h, wherein the amount of sulfonic acid-functionalized UiO-66 type metal-organic framework material was 40 wt% of the amount of polyvinylidene fluoride in the polyvinylidene fluoride solution, and the amount of divinylbenzene was 1.5 wt% of the amount of polyvinylidene fluoride in the polyvinylidene fluoride solution. [P 66614 The amount of [OTf] used is 20 wt% of the sulfonic acid-functionalized UiO-66 type metal-organic framework material.
[0074] The spinning solution was injected into the feeding system of the electrospinning equipment (spinneret diameter of 0.5 mm), and spinning was carried out under the conditions of spinning voltage of 18 kV, receiving distance of 15 cm, and spinning solution flow rate of 1 mL / h to obtain a filament film with a thickness of 150 μm and a number of 150 filaments.
[0075] The silk membrane was immersed in a 2% APTES / ethanol solution for 30 min, then removed and cured at 80℃ for 1 h. It was then rinsed with pure water to obtain a MOF composite membrane that selectively adsorbs rhenium.
[0076] (2) Arsenic removal: In this embodiment, waste acid generated by a smelting enterprise was treated. The waste acid had the following water quality: rhenium 19.4 mg / L, arsenic 3.9 g / L, sulfate 150 g / L, molybdenum 13.2 mg / L, pH 2.1. The pH of the filtered waste acid was adjusted to 4.5 with calcium hydroxide, sodium phosphate was added to a concentration of 0.1 M, and then ferric chloride solution with a concentration of 1.0 M (where the molar ratio of iron to arsenic was 1.5:1) was added dropwise. At the same time, the mixture was slowly stirred at room temperature for 60 min. Depending on the arsenic concentration, ferric chloride solution was added and stirred for another 60 min. This operation was repeated until the arsenic concentration was below 80 mg / L. The mixture was then filtered to obtain solidified arsenic slag and waste acid after arsenic removal.
[0077] (3) Adjust the pH of the arsenic-removed waste acid to 1.5, and then filter it through the MOF composite membrane that selectively adsorbs rhenium (wherein, the membrane flux is 75 L / (m²)). 2 (·h), with a water flow rate of 318 mL / h, a MOF composite membrane for purifying acid and adsorbing rhenium was obtained.
[0078] After adsorption saturation, the rhenium-adsorbed MOF composite membrane was backwashed with an acidic mixed aqueous solution of ethylenediaminetetraacetic acid (EDTA) and sodium chloride (EDTA concentration 0.1 M, sodium chloride concentration 0.1 M, pH 3), then backwashed with water until neutral, and finally backwashed with an alkaline mixed aqueous solution of ammonium chloride and ammonia (ammonium chloride concentration 0.1 M, ammonia concentration 0.1 M, pH 9.0). The backwash solution was collected to obtain a rhenium-rich solution.
[0079] Comparative Example 1 MOF composite membranes that selectively adsorb rhenium were prepared using the method in Example 1, and the membranes were used to treat the same waste acid, except that sodium phosphate was not added during the arsenic removal stage.
[0080] Comparative Example 2 MOF composite membranes selectively adsorbing rhenium were prepared using the method in Example 1, and the membranes were used to treat the same polluted acid, the only difference being that the molar ratio of ZrCl4, 2-sulfonic acid terephthalic acid, and terephthalic acid was 1:0.1:1.
[0081] Comparative Example 3 The MOF composite membrane that selectively adsorbs rhenium was prepared using the method in Example 1, and the membrane was used to treat the same waste acid. The only difference was that no ionic liquid was added when preparing the MOF composite membrane that selectively adsorbs rhenium.
[0082] Comparative Example 4 A MOF composite membrane selectively adsorbing rhenium was prepared using the method in Example 1, and the membrane was used to treat the same waste acid, except that the arsenic removal step was omitted.
[0083] The concentrations of arsenic and rhenium in the waste acid before and after the arsenic removal step in Examples 1-3 and Comparative Examples 1-4 were tested using inductively coupled plasma optical emission spectrometry (ICP-OES), and the removal rates of arsenic and rhenium in the arsenic removal step were calculated. The results are shown in Table 1.
[0084] The concentrations of molybdenum, sulfate, and rhenium in the waste acid before and after filtration through the MOF composite membrane with selective rhenium adsorption were tested using the ICP-OES method, and the membrane permeate rates of molybdenum, sulfate, and rhenium were calculated. The results are shown in Table 1.
[0085] Table 1. Effects of arsenic removal and MOF composite membrane filtration steps in Examples 1-3 and Comparative Examples 1-4
[0086] As shown in Table 1, the arsenic removal rates in Examples 1-4 were all above 98%. In Comparative Example 1, no sodium phosphate was added in the arsenic removal step, resulting in a significant increase in rhenium removal rate, indicating that iron has an adsorption effect on rhenium. The permeate rates of molybdenum, sulfate, and rhenium in Table 1 show that the permeate rate of rhenium in Examples 1-3 was 1.1-3.6%, indicating that rhenium remained in the membrane, thus achieving rhenium enrichment. In Comparative Example 2, the amount of sulfonic acid functional ligand was relatively small, leading to an increase in rhenium permeate rate, indicating that the reduction of sulfonic acid groups reduced the adsorption of rhenium. In Comparative Example 3, no ionic liquid was added, resulting in a higher rhenium permeate rate. This is because the lack of acid-resistant ionic liquid protection for the pores allowed the acid in the contaminants to corrode the membrane. In Comparative Example 4, without an arsenic removal stage, rhenium had the highest permeate rate, because the waste acid contained a high amount of arsenic, and arsenic and rhenium compete for adsorption.
[0087] The MOF composite membrane with selective rhenium adsorption obtained in Examples 1-3 was used to continuously filter arsenic-removed waste acid (according to step (3)) for 500 h, and the membrane permeation rates of molybdenum, sulfate and rhenium were measured. The results are shown in Table 2.
[0088] Table 2. Ion permeation rates of MOF composite membranes selectively adsorbing rhenium obtained in Examples 1-3 after 500 h of continuous operation.
[0089] As shown in Table 2, after 500 hours of continuous operation, the rhenium permeation rate of the MOF composite membrane selectively adsorbing rhenium increased slightly by 1.6-2.9%, while the permeation rate of sulfate remained above 95%, and the permeation rate of molybdenum increased by 2.3-3.1%. This indicates that the MOF composite membrane selectively adsorbing rhenium provided by this invention has excellent stability.
[0090] In this embodiment, to facilitate observation of backwashing efficiency, backwashing was performed once every 100 hours of operation, and the rhenium elution rate was measured. The results are shown in Table 3.
[0091] Table 3. Rhenium elution rate of MOF composite membranes with selective rhenium adsorption obtained in Examples 1-3
[0092] As can be seen from the data recorded in Table 3, the method of the present invention can fully elute the perylene ions from the composite membrane, thereby enabling their recovery.
[0093] The rhenium recovery rate was calculated based on the elution rate and the total amount added, and the results are shown in Table 4.
[0094] Table 4. Rhenium recovery rates of MOF composite membranes with selective rhenium adsorption obtained in Examples 1-3
[0095] As can be seen from Table 4, the MOF composite membrane for selectively adsorbing rhenium provided by the present invention can recover more than 91% of rhenium.
[0096] Although preferred embodiments of the invention have been shown and described, it is conceivable that those skilled in the art can devise various modifications to the invention within the spirit and scope of the appended claims.
Claims
1. A method for preparing a MOF composite membrane that selectively adsorbs rhenium, comprising the following steps: A sulfonic acid-functionalized UiO-66 type metal-organic framework material was dispersed in a polyvinylidene fluoride solution to obtain a metal-organic framework material dispersion. The metal-organic framework material dispersion was mixed with a crosslinking agent to carry out a crosslinking reaction. The resulting reaction solution was then mixed with an acid-resistant ionic liquid to obtain a spinning solution. The spinning solution is subjected to electrospinning to obtain a silk film. After the silk membrane is impregnated in an aminosilane coupling agent solution and then cured, a MOF composite membrane that selectively adsorbs rhenium is obtained.
2. The preparation method according to claim 1, characterized in that, The sulfonate-functionalized UiO-66 type metal-organic framework material was prepared by a method comprising the following steps: Zirconium source, sulfonic acid functional ligand, and terephthalic acid were added to a mixed solvent of N,N-dimethylformamide and acid, and the mixture was sonicated for 15-20 min, followed by a solvothermal reaction. The resulting reaction solution was then subjected to solid-liquid separation to obtain the sulfonic acid-functionalized UiO-66 precursor. The sulfonic acid-functionalized UiO-66 precursor was sequentially washed with N,N-dimethylformamide aqueous solution, replaced with ethanol solvent, and acidified, followed by drying and activation to obtain a sulfonic acid-functionalized UiO-66 type metal-organic framework material.
3. The preparation method according to claim 2, characterized in that, The zirconium source is at least one selected from ZrCl4, ZrOCl4, and Zr(NO3)4; the sulfonic acid functional ligand is at least one selected from 2-sulfonic acid terephthalic acid and sodium 2-sulfonic acid terephthalate; and the acid is at least one selected from glacial acetic acid, formic acid, hydrochloric acid, and benzoic acid. The molar ratio of the zirconium source to the sulfonic acid functional ligand is 1:0.2-0.8, and the molar ratio of the zirconium source to terephthalic acid is 1:0.5-0.
8. The volume ratio of N,N-dimethylformamide to acid is 9-11:1, and the ratio of zirconium source to mixed solvent is 1 mmol: 26-29 mL. The solvothermal reaction is carried out at 115-125℃ for 22-26 h.
4. The preparation method according to claim 2, characterized in that, The volume ratio of N,N-dimethylformamide to water in the N,N-dimethylformamide aqueous solution is (3-4):
1. The acidification involved washing the sulfonic acid-functionalized UiO-66 precursor, after ethanol solvent replacement, with a 0.1 M hydrochloric acid / ethanol solution. The drying process is vacuum drying, and the drying temperature is 140-160℃ for 4-8 hours. The activation is carried out in a protective atmosphere at a temperature of 180-220°C for 5-7 hours.
5. The preparation method according to claim 1, characterized in that, The solvent for the polyvinylidene fluoride solution is N,N-dimethylformamide, and the concentration of the polyvinylidene fluoride solution is 12-15 wt%. The amount of the sulfonate-functionalized UiO-66 type metal-organic framework material used is 30-40 wt% of the amount of polyvinylidene fluoride in the polyvinylidene fluoride solution. The crosslinking agent is at least one of divinylbenzene and ethylene glycol dimethacrylate, and the amount of the crosslinking agent is 1.3-1.7 wt% of the amount of polyvinylidene fluoride in the polyvinylidene fluoride solution. The crosslinking reaction is carried out at room temperature for 25-40 minutes. The acid-resistant ionic liquid is [P] 66614 [OTf], wherein the amount of the acid-resistant ionic liquid used is 18-22 wt% of the sulfonic acid-functionalized UiO-66 type metal-organic framework material.
6. The preparation method according to claim 1, characterized in that, The electrospinning spinneret has a diameter of 0.4-0.6 mm, a spinning voltage of 18-22 kV, a receiving distance of 15-18 cm, a spinning solution flow rate of 0.8-1.2 mL / h, and a fiber film thickness of 140-160 μm. The aminosilane coupling agent in the aminosilane coupling agent solution includes at least one of 3-aminopropyltriethoxysilane and N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, the concentration of the aminosilane coupling agent solution is 1.8-2.5 wt%, and the solvent of the 3-aminopropyltriethoxysilane solution is at least one of ethanol and isopropanol. The impregnation time is 25-40 min, the curing temperature is 60-80℃, and the curing time is 0.8-1.2 h.
7. A MOF composite membrane for selectively adsorbing rhenium prepared by the preparation method according to any one of claims 1-6.
8. The application of the MOF composite membrane for selectively adsorbing rhenium as described in claim 7 in the recovery of rhenium from waste acid.
9. The application according to claim 8, characterized in that, The application includes the following steps: The waste acid after removing suspended solids is then subjected to arsenic removal to obtain solidified arsenic slag and arsenic-removed waste acid. After adjusting the pH of the arsenic-removed waste acid to 1.3-1.7, it is filtered through the MOF composite membrane that selectively adsorbs rhenium to obtain purified acid and the rhenium-adsorbing MOF composite membrane. The rhenium-adsorbed MOF composite membrane was backwashed sequentially with acidic washing solution, water, and alkaline washing solution to obtain a rhenium-rich solution.
10. The application according to claim 9, characterized in that, The arsenic removal process includes the following steps: adjusting the pH of the waste acid to 3.5-4.5, then adding sodium phosphate to a concentration of 0.02-0.1 M, then adding ferric chloride solution dropwise until the arsenic concentration is below 80 mg / L, and then filtering; wherein the concentration of the ferric chloride solution is 0.5-1.0 M. The acidic washing solution is an acidic mixed aqueous solution of ethylenediaminetetraacetic acid (EDTA) and sodium chloride, wherein the concentration of EDTA is 0.09-0.11 M, the concentration of sodium chloride is 0.09-0.11 M, and the pH of the acidic mixed aqueous solution is 2-4. When backwashing with water, backwash until the washing solution is neutral. The alkaline washing solution is an alkaline mixed aqueous solution of ammonium chloride and ammonia, wherein the concentration of ammonium chloride is 0.09-0.11 M, the concentration of ammonia is 0.09-0.11 M, and the pH of the alkaline mixed aqueous solution is 8.8-9.2.
Citation Information
Patent Citations
Method for preparing ammonium perrhenate through extracting from coppersmelting exhaust gas washing acid pickle
CN102502855A
Separation and recovery method of rhenium in sulfuric acid waste liquid
CN105803208A
Method for separating rhenium from rhenium-containing solution by adopting anion exchange resin
CN119464782A
Rhenium extraction agent composition, rhenium extraction agent and rhenium extraction method
CN119956131A
MOF / PIM-1 in-situ crosslinked matrix membrane and preparation method thereof
CN110433668A
Cited By
Composite solid electrolyte for energy storage lithium ion battery as well as preparation method and application of composite solid electrolyte
CN122291678A
